2002
DOI: 10.1212/01.wnl.0000036610.36834.e0
|View full text |Cite
|
Sign up to set email alerts
|

The association of incident dementia with mortality in PD

Abstract: Incident dementia has an independent effect on mortality when controlling for EPS severity. The development of dementia is associated with a twofold increased mortality risk in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
154
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(168 citation statements)
references
References 62 publications
6
154
2
6
Order By: Relevance
“…In accordance to one study 10 (but not another 2 ), we found an association between bradykinesia and poor functional outcomes. As in our study, previous research has found gait disorder to be associated with increased mortality in patients with PD 37 and even in nondemented elderly. 38 Postural and gait The models of the 1st and 2nd row included total motor signs sum score as time-dependent predictor.…”
supporting
confidence: 87%
“…In accordance to one study 10 (but not another 2 ), we found an association between bradykinesia and poor functional outcomes. As in our study, previous research has found gait disorder to be associated with increased mortality in patients with PD 37 and even in nondemented elderly. 38 Postural and gait The models of the 1st and 2nd row included total motor signs sum score as time-dependent predictor.…”
supporting
confidence: 87%
“…Furthermore, NCDs are a common illness in the elderly, and they represent one of the most important factors in disability and mortality (2). The prevalence of NCDs is estimated to range from 2% to 8% in the elderly population (3).…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, the impact of MCI and dementia in pa-tients with PD at any given stage of the disease is substantial, with adverse consequences for functioning, 7 psychiatric morbidity, caregiver burden, 8 and mortality. 9 At present, there is much to be elucidated with regard to the etiology of cognitive impairment in PD. Initially, dementia in PD was described as subcortical.…”
mentioning
confidence: 99%